Functional comparison of plasma-membrane Na+/H+ antiporters from two pathogenic Candida species - Krauke, Yannick; Sychrová, Hana (BMC microbiology, 2008)
BACKGROUND: The virulence of Candida species depends on many environmental conditions. Extracellular pH and concentration of alkali metal cations belong among important factors. Nevertheless, the contribution of transporters mediating the exchange of alkali metal cations for protons across the plasma membrane to the cell salt tolerance and other physiological properties of various Candida species has not been studied so far. RESULTS: The tolerance/sensitivity of four pathogenic Candida species to alkali metal cations was tested and the role of one of the cation transporters in that tolerance (presumed to be the plasma-membrane Na+/H+ antiporter) was studied. The genes encoding these antiporters in the most and least salt sensitive species, C. dubliniensis and C. parapsilosis respectively, were identified, cloned and functionally expressed in the plasma membranes of Saccharomyces cerevisiae cells lacking their own cation exporters. Both CpCnh1 and CdCnh1 antiporters had broad substrate specificity and transported Na+, K+, Li+, and Rb+. Their activity in S. cerevisiae cells differed; CpCnh1p provided cells with a much higher salt tolerance than the CdCnh1 antiporter. The observed difference in activity was confirmed by direct measurements of sodium and potassium efflux mediated by these antiporters. CONCLUSION: We have cloned two genes encoding putative Na+/H+ antiporters in C. parapsilosis and C. dubliniensis, and characterized the transport properties of encoded proteins. Our results show that the activity of plasma-membrane Na+/H+ antiporters is one of the factors determining the tolerance of pathogenic Candida species to high external concentrations of alkali metal cations.
Keywords: lithium; membránové proteiny; alkalické kovy; Substrate Specificity; Financing, Organized; Na(+)-H(+) antiport; Protein Structure, Secondary; Superoxide Dismutase; draslík; substrátová specifita; Base Sequence; Cations; Microscopy, Fluorescence; soli; Membrane Proteins; Metals, Alkali; proteiny přenášející kationty; molekulární sekvence - údaje; Salts; Lithium; Saccharomyces cerevisiae - proteiny; Molecular Sequence Data; financování organizované; sekvence nukleotidů; Fungal Proteins; kationty; Saccharomyces cerevisiae Proteins; Cation Transport Proteins; Candida; fluorescenční mikroskopie; Potassium; Sodium-Hydrogen Exchangers; fungální proteiny; sekundární struktura proteinů; Saccharomyces cerevisiae; superoxiddismutasa